Acciones educativas de enfermería a mujeres en edad fértil como recurso para la prevención de la hipertensión gestacional - Estefanía Belén, Caicedo López (2022)
ABSTRACT The aim of this research was to determine the educational actions of nursing to women of childbearing age as a resource for the prevention of gestational hypertension. High blood pressure in pregnancy is a public health problem, because it triggers a complicated prognosis at delivery and during the prenatal stage, causing chronic hypertensive diseases, cardiac pathologies, stroke, and even pathologies in the newborn, thus increasing maternal and neonatal mortality. A bibliographic review was carried out in which information compiled on national and universal scientific support, disseminated in websites such as: Google Scholar, Scielo, Infomed, Dialnet, Medigraphic and Elsevier, as well as visits to official websites of the World Health Organization (WHO), Ministry of Public Health (MSP) and the Pan American Health Organization (PAHO). At the end of the research, it concluded that the nursing actions aimed at fertile women to prevent gestational hypertension are prenatal care through family planning with the use of contraceptive methods according to the woman's condition. In addition, promoting adiet rich in calcium, oral and personal hygiene, physical exercise based on flexibility, aerobic and strength, avoiding the consumption of toxic substances, attending medical check-ups for the treatment of predisposing comorbidities; so that through the application of the nursing process and the use of clinical guidelines, interventions can be planned in order to promote self-care in patients. Key words: Pregnancy-induced hypertension, women, fertile period. Firmado electrónicamente por: MARITZA DE LOURDES CHAVEZ AGUAGALLO Reviewed by: Mgs. Maritza Chávez Aguagallo ENGLISH PROFESSOR c.c. 0602232324